Religious Value-Based Guidance and Counseling and Its Influence on Students’ Emotional Regulation: A Descriptive Qualitative Inquiry - Denok Setiawati; Elisabeth Christiana; Retno Tri Hariastuti; Sherrin Nurlita Widya; Evi Winingsih; Devi Ratnasari; Farid Ilhamuddin (Universitas Negeri Padang, 2026)
Guidance and counselling services are vital in helping students manage their emotions, including those shaped by religious values. This descriptive study aims to demonstrate the effect of guidance and counselling rooted in religious values on students' emotional regulation. Data collection methods included interviews, documentation, and descriptive assessment scales on emotional regulation. The participants were selected through purposive non-random sampling, comprising 16 students who had received guidance and counselling on religious values and emotional regulation, as well as 2 counsellors providing these services. The analysis employed specific techniques. The counsellors' services involved guidance and counselling incorporating religious values such as patience, self-reflection, sincerity, striving for improvement, and faith in what Allah provides. These services contributed to improved emotional regulation by helping students identify causes of negative emotions, change thought patterns, and select activities that produce positive emotions. The religious values integrated into the guidance and counselling included classical guidance, group guidance, individual counselling, and group therapy. Students demonstrated increased capacity to regulate their emotions, especially when confronting changing situations that evoke emotions, with the least effective strategy being to divert attention from triggers of negative emotions. Based on these findings and the noted limitations, further research with a larger, more diverse population is essential. It is also important to explore how counselling services grounded in religious values can further enhance emotional regulation across diverse contexts.